The Influence of Western Feminism on Islamic Family Law Renewal in Iran: Studies of Pre and Post Reform of Iran - Shaleh, Ridwan (Al-Bayyinah, 2023)
This paper tries to examine the dynamics of family law in Iran, where changes in Islamic family law in Iran occurred during the 1979 revolution after the collapse of the pahlavi regime. Which in that year Ayatollah Khomeini formulated Islamic family law and raised the status of women. However, until 1980 Iranian women had not felt the change, which gave rise to a women's movement thatprotested against it. The method of writing this article uses library research by digging up information related to the theme of the study. The findings of this paper explain that the emergence of feminism thought in Iran was propounded by europeanswho in 1980 were mostly europeansand they judged some of the habits of the Iranian family and society which for them were against women. So this is what pioneered the movement against feminism in Iran in finding out about gender The feminist movement against Islamic family law in Iran is motivated by many laws that are detrimental to women, because these laws are the result of male scholars, so many of them voice their dissatisfaction with these laws.